Using biometric data to protect information - K. N. Vlasov; O. V. Tolstykh; O. V. Isaev (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. An urgent task is to evaluate the system for protecting access to information while minimizing errors, based on the use of human biometric data. It is necessary to evaluate and compare methods and solutions of biometric authentication, and the possibility of combining them.Method. The method for assessing and comparing biometric authentication methods and solutions is based on practical experience and regulatory and technical documentation on the use of biometric data for information security purposes. It is necessary to complicate the possibility of unauthorized access to information. At the same time, improving the system should not worsen the comfort of a legitimate user when trying to access. The remaining tasks are to reduce entry time and simplify the system.Result. An assessment of biometric authentication methods and solutions was carried out and a solution was proposed for the development of biometric authentication systems to protect against unauthorized access, the key criteria in which were the complexity of hacking, user comfort, login time and simplification of the system.Conclusion. The optimal solution in the development of biometric authentication systems would be to use multi-factor authentication using dynamic parameters of the access subject. A modern biometric authentication system should be installed taking into account the level of security required at the time.